Keragaman Kandungan Lemak Nabati Spesies Shorea Penghasil Tengkawang dari Beberapa Provenans dan Ras Lahan - Budi Leksono; Lukman Hakim (Jurnal Ilmu Kehutanan, 2018)
Buah tengkawang merupakan salah satu hasil hutan bukan kayu bernilai tinggi dan merupakan salah satu komoditi eksporsebagai bahan baku lemak nabati, industri kosmetik, dan substitusi lemak coklat. Indonesia memiliki sekitar 13 spesies pohon penghasil tengkawang yang tersebar di Kalimantan dan sebagian kecil di Sumatera, namun sebagian besar telah masuk dalam kategori terancam punah. Untuk tindakan konservasi dan meningkatkan kandungan lemak nabati tengkawang, perlu diketahui potensi kandungan lemak dan sifat fisiko kimia dari setiap spesies dan provenan. Buah tengkawang dikoleksi pada saat musim panen raya spesies shorea penghasil tengkawang pada tahun 2010 di Kalimantan dan Jawa. Analisis kandungan lemak nabati tengkawang dilakukan terhadap empat spesies shorea penghasil tengkawang (S. macrophylla, S. gysbertsiana, S. stenoptera, S. pinanga) yang berasal dari empat provenans dan ras lahan (Gunung Bunga dan Sungai Runtin-Kalimantan Barat, Bukit Baka-Kalimantan Tengah, Haurbentes-Jawa Barat). Sebelas kombinasi spesies-provenan diambil sampel buahnya untuk diekstrasi guna mengetahui kandungan lemak dan sifat fisiko kimia tengkawang (kadar air, bilangan asam, dan kadar asam lemak bebas). Terdapat keragaman yang tinggi di antara kombinasi spesiesprovenans tengkawang untuk empat parameter yang diuji, termasuk kandungan lemak dan kadar air biji tengkawang. Kandungan lemak tertinggi dengan kadar air terendah dihasilkan oleh S. stenoptera dari Haurbentes (Jabar) dan S. pinanga dari Bukit Baka (Kalimantan Tengah). Kedua kombinasi spesies-provenan tersebut direkomendasikan sebagai materi genetik untuk dikembangkan dalam program konservasi eks-situ dan program pemuliaan tanaman hutan dalam pembangunan sumber benih unggul pada kondisi lingkungan yang hampir sama dengan kedua provenans dan ras lahan tersebut.Variation in Illipe Nut's Fat Yield of Tengkawang-producing Shorea from Several Provenances and Land RacesAbstractIllip (tengkawang) nut is a non-wood forest product which has a high economic value and one of export commodities as raw material for illipe nut's fat, cosmetics, and substitution of chocolate fat. Indonesia has 13 species of tengkawang-producing shorea distributed in Kalimantan and some small parts of Sumatra. Most of them are categorized as threatened species. To conserve and improve the species for illip nut's fat, it is important to assess the potential of fat yield and physical-chemical properties for each species and provenance. Fruit collection was conducted during fruit season in Kalimantan and Java in 2010. The fruits were collected from four species of tengkawangproducing shorea (i.e. S.macrophylla, S. gysbertsiana, S. stenoptera, S. pinanga) originated from 4 provenances and land races (Gunung BungaWest Kalimantan, Sungai Runtin-West Kalimantan, Bukit Baka-Central Kalimantan, and Haurbentes-West Java). Fruit samples from eleven combinations of species-provenances were extracted to assess fat yield and physical-chemical properties (i.e. moisture content, acid number and free fatty acid). Variation between species-provenances combination was high for all parameters tested, including the illipe nut's fat yield and moisture content. The highest fat yield with lowest moisture content was found in S. stenoptera from Haurbentes (West Java) and S. pinanga from Bukit Baka (Central Kalimantan). Both species-provenance combinations are recommended as genetic material to be developed in the program of ex-situ conservation as well as tree improvement program for the establishment of best seed sources in the same environment condition as the respected provenances.